Growth performance and nutrient utilization of Clarias gariepinus (Burchell) fry fed processed sweet potatoe(Ipomea batata) (2007)
Maize is an expensive energy source for feedstuff in fish management especially during the off-season, hence the need to source and utilize other cheaper and non-conventional energy sources. This study investigated the growth performance of Clarias gariepinus fry fed processed sweet potato meal as an energy source and its effect on the hematological values. Three experimental diets were compounded such that maize was 100% energy source in Diet 1 (Control). In diets 2 and 3, maize was replaced with sweet potatoes tuber (SPT) and sweet potato peel (SPP), respectively at 25% inclusion level. The diets were fed at 5% body weight to the C. gariepinus fry (0.21 ±0.03) in polystyrene net cages suspended in 3 concrete tanks (2x3x1.2)m3 for 42 days in triplicates. Growth, nutrient utilization and hematological parameters were measured. The Mean Weight Gain (MWG) of the fry fed the maize based diet (1.96) was significantly higher (p<0.05) than the fry fed SPT (1.37) and SPP (1.27) respectively. The MWG of fry fed diets 2 and 3 were not significantly different from each other. The FCR of the control and the SPT based diets were not significantly different from each other but both were significantly different (p<0.05) from fish fed the SPP diet. The Growth Efficiency Feed Conversion (GEFC) values of the 3 diets (0.50, 0.51, and 0.40) respectively are not significantly different from each other. However, the PER and the survival rates were significantly better in fry fed the SPT based diet (0.51: 95%) than in fry fed the maize based diet (0.50: 92%) and the SPP based diet(0.40: 82%) respectively. The haemotology results showed that the fry fed the control diet had the lowest MCV and WBC counts while the fry fed SP based diets manifested moderately severe normocyctic normochromic anemia and leucocytosis, which means that the maize diet showed better hematological indices. This study showed that SP based diets have potential as substitute for maize. Maize based diet and especially the SPT, have similar FCR, dietary energy, GEFC values.